1993
DOI: 10.3168/jds.s0022-0302(93)77620-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Antioxidants, and Animal Function

Abstract: Reactive oxygen metabolites generated during normal metabolism and metabolism stimulated by xenobiotics can enter into reactions that, when uncontrolled, can impair performance of dairy cows. Direct effects include peroxidative changes in membranes and other cellular components. Indirectly, competitive consumption of reducing equivalents can interfere with important metabolic functions and divert glucose from other pathways by inducing the monophosphate shunt. Normally, the body is protected by a wide range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
480
1
54

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(545 citation statements)
references
References 39 publications
10
480
1
54
Order By: Relevance
“…The limited effect of dexamethasone on both oxidative stress parameters considered in this study (GPx and TAS) might be explained by the animal's attempt to maintain the balance between plasma pro-oxidant and antioxidant constituents (Miller et al, 1993;Bourdon and Blanche, 2001), which implies a dynamic response. For this reason, GPx and TAS do not appear to be useful biochemical tools for the detection of cattle treated illegally by corticosteroids.…”
Section: Discussionmentioning
confidence: 94%
“…The limited effect of dexamethasone on both oxidative stress parameters considered in this study (GPx and TAS) might be explained by the animal's attempt to maintain the balance between plasma pro-oxidant and antioxidant constituents (Miller et al, 1993;Bourdon and Blanche, 2001), which implies a dynamic response. For this reason, GPx and TAS do not appear to be useful biochemical tools for the detection of cattle treated illegally by corticosteroids.…”
Section: Discussionmentioning
confidence: 94%
“…They play a protective role against ROS, thus reducing the lipoperoxides evidenced by the decrease in plasma MDA. The reduction in ROMs and lipid peroxidation (TBARS) can be due both to the direct action of the antioxidant verbascoside, which captures free radicals during the propagation of a chain reaction, and a phase-lock initiation of oxidation by inhibiting pro-oxidant enzymes (Miller et al, 1993;Kamiloglu et al, 2006). These results are in agreement with those reported by Corino et al (2007b) on weaned piglets fed a verbascosidesupplemented diet.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that dietary supplementation of probiotics with antimicrobial and antioxidant properties may be a promising strengthening agent for increasing pathogen resistance in animals. Reproduction is likely to fail long before life is endangered by deficiency of any required nutrient, including dietary antioxidants (Miller and Brzezinska-Slebodzinska, 1993). To date, no study has been found reporting on the effects of antioxidative probiotics on reproductive performance and oxidative status in animals, and only preliminary reports are available.…”
Section: Introductionmentioning
confidence: 99%